The Route to Freedom: The Significance of the Mississippi River in Mark Twain’s The Adventures of Huckleberry Finn - Maafa, Sofiane (LANGUAGE ART, 2023)
The antebellum period had witnessed some heavy waves of slaves escaping from the American Southern pro-slavery states to what was known as the “Free States” in the North. There were several routes for these slaves to take while pursuing their freedom; one of the major routes toward freedom was the Mississippi River. The present article tackles the very symbolism of the Mississippi River according to the American author Mark Twain together with other authors. The article will, then, seek to analyze the different symbolisms of the Mississippi River in Twain’s The Adventures of Huckleberry Finn; this including the dangers facing both Huck and Jim every time they stopped at the river’s banks. In the end, the article will conclude with the idea that the river did not only serve as a route toward freedom, but also it brought the two conflicting races together; thus helping Huck to get away from civilization and Jim to escape captivity.